Effects of calcium-magnesium carbonate and calcium-magnesium hydroxide as supplemental sources of magnesium on ruminal microbiome - Arce Cordero, José Alberto (2022)
Our objective was to evaluate the inclusion of calcium-magnesium carbonate [CaMg(CO3 ) 2 ] and calcium-magnesium hydroxide [CaMg(OH)4 ] in corn silage-based diets and their impact on ruminal microbiome. Our previous work showed a lower pH and molar proportion of butyrate from diets supplemented with [CaMg(CO3 ) 2 ] compared to [CaMg(OH)4 ]; therefore, we hypothesized that ruminal microbiome would be affected by Mg source. Four continuous culture fermenters were arranged in a 4 × 4 Latin square with the following treatments defined by the supplemental source of Mg: 1) Control (100% MgO, plus sodium sesquicarbonate as a buffer); 2) CO3 [100% CaMg(CO3 ) 2 ]; 3) OH [100% CaMg(OH)4 ]; and 4) CO3 /OH [50% Mg from CaMg(CO3 ) 2 , 50% Mg from CaMg(OH)4 ]. Diet nutrient concentration was held constant across treatments (16% CP, 30% NDF, 1.66 MCal NEl/kg, 0.67% Ca, and 0.25% Mg). We conducted four fermentation periods of 10 d, with the last 3 d for collection of samples of solid and liquid digesta effluents for DNA extraction. Overall, 16 solid and 16 liquid samples were analyzed by amplification of the V4 variable region of bacterial 16S rRNA. Data were analyzed with R and SAS to determine treatment effects on taxa relative abundance of liquid and solid fractions. Correlation of butyrate molar proportion with taxa relative abundance was also analyzed. Treatments did not affect alpha and beta diversities or relative abundance of phylum, class and order in either liquid or solid fractions. At the family level, relative abundance of Lachnospiraceae in solid fraction was lower for CO3 and CO3 /OH compared to OH and Control (P < 0.01). For genera, abundance of Butyrivibrio (P = 0.01) and Lachnospiraceae ND3007 (P < 0.01) (both from Lachnospiraceae family) was lower and unclassified Ruminococcaceae (P = 0.03) was greater in CO3 than Control and OH in solid fraction; while abundance of Pseudobutyrivibrio (P = 0.10) and Lachnospiraceae FD2005 (P = 0.09) (both from Lachnospiraceae family) and Ruminobacter (P = 0.09) tended to decrease in CO3 compared to Control in liquid fraction. Butyrate molar proportion was negatively correlated to Ruminococcaceae (r = –0.55) in solid fraction and positively correlated to Pseudobutyrivibrio (r = 0.61) and Lachnospiraceae FD2005 (r = 0.61) in liquid. Our results indicate that source of Mg has an impact on bacterial taxa associated with ruminal butyrate synthesis, which is important for epithelial health and fatty acid synthesis.